FORMULATION DEVELOPMENT AND STABILITY OF MORINGA OLEIFERA SEED OIL NANOEMULSION-BASED HAIR SERUM - MUTMAINAH; NUGROHO, AKHMAD KHARIS; HERTIANI, TRIANA; ADHYATMIKA (International Journal of Applied Pharmaceutics, 2025)
Objective: Synthetic drugs for treating hair loss often cause side effects. M. oleifera seed oil has shown potential in preventing hair loss; however, its oily and sticky texture limits its practicality for application. This study aims to develop a well-formulated and stable nanoemulsion-based hair serum containing M. oleifera seed oil at 4 °C and 40 °C. Methods: The study utilized hair serum formulations containing nanoemulsified M. oleifera seed oil at concentrations of 10%, 20%, and 30%. The physical characteristics, including organoleptic properties, pH, viscosity, spreadability, and adhesiveness, were evaluated. Additionally, stability testing was conducted using a cycling test at 4 °C and 40 °C over six cycles. Results: Variations in nanoemulsion concentration in the hair serum influenced pH, viscosity, adhesiveness, and spreadability, all of which met the required criteria. Higher concentrations of nanoemulsified M. oleifera seed oil resulted in lower pH, viscosity, and adhesiveness while increasing spreadability. Stability testing showed no statistically significant differences (p>0.05) in pH, viscosity, adhesiveness, or spreadability before and after the test. Conclusion: The nanoemulsion-based hair serum formulation remained stable and effectively reduced the sticky and oily texture of M. oleifera seed oil, making it a more practical alternative for hair loss treatment.